High‐stability two‐dimensional perovskite LaNb2O7 for high‐performance wide‐temperature (80–780 K) UV light detection and human motion detection - Yong Zhang; Jian Yao; Lin Wang; Long Chen; Junyi Du; Pin Zhao; Qing Guo; Zhen Zhang; Lixing Kang; Xiaosheng Fang (InfoMat)
Abstract The unity of high‐stability and high‐performance in two‐dimensional (2D) material devices has consistently posed a fundamental challenge. Halide perovskites have shown exceptional optoelectronic properties but poor stability. Conversely, oxide perovskites exhibit exceptional stability, yet hardly achieve their high photoelectric performances. Herein, for the first time, high‐stability 2D perovskite LaNb2O7 (LNO) is engineered for high‐performance wide‐temperature UV light detection and human motion detection. High‐quality LNO nanosheets are prepared by solid‐state calcination and liquid‐phase exfoliation technique, resulting in exceptional stability against high temperature, acid, and alkali solutions. As expected, individual LNO nanosheet device achieves ultra‐wide temperature (80–780 K) and ultra‐high (3.7 × 104 A W−1 at 780 K) UV light detection. Importantly, it shows high responsivity (171 A W−1), extraordinary detectivity (4 × 1012 Jones), fast speed (0.3/97 ms), and long‐term stability under ambient conditions. In addition, wafer‐scale LNO film devices can be used as pixel array detectors for UV imaging, and large‐area flexible LNO film devices exhibit satisfactory photodetection performance after repeated bending tests. Interestingly, LNO nanosheets also exhibit distinct piezoelectric characteristics, which can serve as high‐sensitivity stress sensors for human motion detection. These encouraging results may pave the way for more innovative advances in 2D perovskite oxide materials and their diverse applications.